Identification of electrode degradation by carbon corrosion in polymer electrolyte membrane fuel cells using the distribution of relaxation time analysis. (10th May 2022) - Kwon, JunHwa; Choi, Pilsoo; Jo, Seunghyun; Oh, Hyunjun; Cho, Ki-Yeop; Lee, Youn-Ki; Kim, Subin; Eom, KwangSup
Highlights: The diagnostic method of cell degradation by carbon corrosion is studied. Load cycling and high potential holding ASTs are performed. Two typical ASTs induce the distinct degradation behaviors and performance decay rates. The distribution of relaxation time (DRT) is used for diagnosis of the electrode degradation. The variation of the specific peak tau reflects the deteriorated electrode condition. Abstract: Carbon corrosion reactions have a tremendous impact on the performance and durability of polymer electrolyte membrane fuel cells (PEMFCs). The impetuses for the carbon corrosion reactions and the degradation behaviors that arise from them vary based on the operating conditions of polymer electrolyte membrane fuel cells (PEMFCs). In this study, two different accelerated stress test (AST) protocols, (ⅰ) a load cycling test between 0.4 and 0.95 V vs. RHE and (ⅱ) a high potential holding test (1.4 V vs. RHE), are performed, and distribution of relaxation time (DRT)-based impedance analyses are conducted to identify the major features of degraded electrodes, resulting in different performance decay rates. Specifically, we focus on the variations in the specific relaxation time, reflecting that the overall electrode degradation arises from the deformation of the electrode structure, the generation of functional groups on the supporting carbon, and loss of catalyst. It is notable that the contrasting degradation behaviors exhibited during two different ASTs result in distinct performance decay rates, and it can be differentiated by the opposite shifts of DRT-peak tau in relaxation time domain. The electrochemical results are also supported by postmortem ex situ surface analyses of deteriorated MEAs to identify the source of performance decays during ASTs.